Malaysia Airlines cabin crew's characteristics and coping mechanisms towards protective behaviour - Jettey, Jeff Nor (Kulliyyah of Information and Communication Technology, Internationai Islamic University Malaysia, 2015)
Airline cabin crew are a special group of people who, besides providing services for passengers, are now, more than ever, responsible to handle security and safety situations. As such, security procedures and awareness training (SPAT) has been a must for cabin crew which not only focuses security on-board the aircraft but also when on the ground and personal safety. Against this backdrop, this research explores the perceptions of Malaysia Airlines cabin crew's characteristics and coping mechanisms. The research uses the Protection Motivation Theory (PMT). Coping mechanism, in this research, is defined as a cabin crew's perceived severity, perceived vulnerability, response efficacy, and self-efficacy. The research adopted a convenient sampling using a self-administered questionnaire. In total, 107 responses made by cabin crew were analysed. There was evidence to suggest that Malaysia Airlines cabin crew rate themselves highly on their coping mechanisms. On relationship among these coping mechanism factors, there is a significantly modest relationship between perceived vulnerability and response efficacy and a significantly modest relationship between response efficacy and self-efficacy. But, the relationship between perceived vulnerability and self-efficacy is not significant and weak. In terms of cabin crew individual's characteristics, there is evidence that shows a statistically significant difference in response efficacy for cabin crew's years of service. Implications of this research are discussed in the dissertation.